Electrochemical Lossy Mode Resonance‐based Fiber Optic Sensing for Electroactive Species. Issue 3 (9th September 2022) - Okazaki, Takuya; Yoshioka, Masaki; Orii, Tatsuya; Taguchi, Akira; Kuramitz, Hideki; Watanabe, Tomoaki
Abstract: We present an electrochemical‐lossy mode resonance (LMR) sensing method that detects refractive indices and electroactive species. The LMR peaks of indium‐tin‐oxide in the transmittance‐wavelength spectra were significantly shifted as the applied potential between 1.0 and −0.5 V at 209 nm/V. The modulation was exploited for sensing the refractive index and electroactive species (ferrocyanide and methylene blue) in two ways: peak‐wavelength tracking and potential scanning. The potential‐scanning technique produced clear potential LMR peaks in the transmittance‐potential spectra for the first time, which were corresponded to the external refractive index. Meanwhile, the limits of detection of ferrocyanide and methylene blue were 7.5 and 25.3 μM, respectively, in peak‐wavelength tracking and 18.2 and 20.8 μM, respectively, in the potential scanning technique. Abstract :